L'utilizzo del podcasting nella didattica universitaria. - Giovanni Moretti; Arianna Morini (LED Edizioni Universitarie, 2020)
In higher education, podcasting is establishing itself as a strategic multimedia resource for training. Research in the educational and didactic field, both in the national and international context, has revealed strength points and critical issues relating to the use of podcasting. The paper presents the results of the research carried out within the Online Degree Course in Educational Sciences of the Department of Education, University of Roma Tre. The main objective of the research was to verify whether the audio podcast could be considered an effective tool to enhance the student learning process and to qualify university distance teaching. The exploratory empirical research included an in-depth study on the use of audio podcasts in teaching and the introduction of different types of podcasts to verify their effectiveness. The data were collected through the use of questionnaires and focus groups. The main results of the research show that the integrated use of a wide variety of podcasts is strategic to improve the quality of the teaching-learning process.